Elementary Students’ Conceptual Understanding Ability in Science: Insights and Implications - Gehan, Yasmin; Suhandi, Andi; Mardiah, Dede; Salshabylla, Dewi Mayang; Ulfiyani, (International Conference on Elementary Education, 2025)
One important aspect in science learning in elementary school is students' ability to understand science concepts. Science learning in elementary school aims to improve students' positive attitudes in solving problems in the community through observation, question and answer activities, and data analysis. This study aims to describe elementary students' understanding of science concepts through targeted assessment aligned with key indicators of conceptual understanding in science. This study used quantitative approach with a survey method, the data in this study were taken from the distribution of tests to respondents. Data was collected through concept understanding tests to gain a view of elementary school students' conceptual understanding in science. The implication of this study is to know and describe the level of science concept understanding possessed by 4th grade elementary school students through the results of the tests given systematically and objectively. The data which obtained will be analyzed to determine the extent to which students have mastered the science concepts that have been taught. The results of the study obtained from the the data distribution are in the form of a science concept understanding test. It is known that the average score was 49.14 with the lowest score of 18.75 and the highest score of 87.50. Overall, it can be concluded that the understanding of science concepts of grade IV students in the 2024/2025 academic year is included in the low category because the average score is 49.14